2021
DOI: 10.1080/19490976.2021.1972757
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan-induced alterations of the gut microbiome protects mice against Citrobacter rodentium infection and intestinal inflammation

Abstract: Hyaluronan is a glycosaminoglycan polymer that has been shown to play an important role in homeostasis of the gastrointestinal tract. However, its mechanistic significance in gastrointestinal epithelial barrier elements remain unexplored. Here, our results revealed that hyaluronan treatment resulted in significant changes in the gut microbiota in mice. To demonstrate the functional consequences of hyaluronan-treatment and hyaluronan-induced microbiota alterations, Citrobacter rodentium- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…HA is widely applied in the commercial field, such as skin care, cosmetic products, eye drops, and health supplements for various medicinal purposes ( 20 , 31 , 32 ). However, the physiological effect of the ingested HA is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HA is widely applied in the commercial field, such as skin care, cosmetic products, eye drops, and health supplements for various medicinal purposes ( 20 , 31 , 32 ). However, the physiological effect of the ingested HA is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This finding supports the notion that HA could be readily fermented by the host's gut microbes and elicited various biological functions in the host. A piece of good evidence came from a recent report showing HA could alter gut microbiome composition and metabolites in mice, in turn, effectively reducing enteric infection and inflammation ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although hyaluronic acid in the brain is associated with demyelinated lesions, 48 intestinal hyaluronic acid is known to decrease intestinal permeability by upregulating tight junction protein expression. 49 Hyaluronan has also been shown to greatly enrich the abundance of Akkermansia muciniphila, 49 a bacterium which is associated with MS but has only recently been linked to lower disability, and the potentially compensatory decreased immune response and amelioration of experimental autoimmune encephalomyelitis. 50 These factors all point to the ability for FMT to potentially exert clinically significant protective and preventative functional alterations to the MS microbiota.…”
Section: Adverse Eventmentioning
confidence: 99%
“…S. thermophilus and HA have positive regulatory effects on the intestinal barrier. 49,50 This encouraged us to study the effects of coated S. thermophilus on the mucus barrier produced by mucin of goblet cells. PAS staining of distal colon tissues of mice showed that there was no difference in the number of goblet cells between the HA group and the control group, but the numbers of goblet cells in the WT and WT + HA groups were significantly increased (to around 16 goblet cells per crypt).…”
Section: Construction Of S Thermophilus Coated With Endogenous Hamentioning
confidence: 99%